The Impact of Delays in Reporting on the Recovery and Interpretation of Sperm Evidence in Sexual Assault Cases in Bangkok, Thailand - Chris Siriraj (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: The timely reporting of sexual assault cases is critical for the preservation and effective analysis of forensic evidence, especially sperm evidence. In Bangkok, Thailand, delays in reporting are common due to various socio-cultural factors. This study aimed to investigate the impact of such delays on the recovery and interpretation of sperm evidence in sexual assault cases. Methods: A retrospective analysis was conducted on 150 sexual assault cases reported in Bangkok between 2018 and 2023. Cases were categorized based on reporting delay: less than 24 hours, 24-72 hours, and more than 72 hours. The recovery rates of sperm from various anatomical sites and the quality of DNA profiles obtained were compared across the groups. Additionally, a survey was conducted among forensic practitioners in Bangkok to assess their perceptions of the challenges associated with delayed reporting. Results: The study found a significant decline in sperm recovery rates with increasing reporting delays. In cases reported within 24 hours, sperm recovery rates were highest, particularly from vaginal swabs. The quality of DNA profiles obtained also showed a similar trend, with delays leading to increased degradation and difficulties in interpretation. The survey revealed that forensic practitioners perceive delayed reporting as a major challenge, impacting their ability to provide conclusive evidence in sexual assault cases. Conclusion: Delays in reporting sexual assault cases in Bangkok significantly impact the recovery and interpretation of sperm evidence. Efforts to encourage prompt reporting, coupled with improved forensic techniques for analyzing degraded samples, are crucial for enhancing the investigation and prosecution of sexual assault cases in the region.